2014
DOI: 10.1101/008144
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The genomic landscape of polymorphic human nuclear mitochondrial insertions

Abstract: The transfer of mitochondrial genetic material into the nuclear genomes of eukaryotes is a well-established phenomenon. Many studies over the past decade have utilized reference genome sequences of numerous species to characterize the prevalence and contribution of nuclear mitochondrial insertions to human diseases. The recent advancement of high throughput sequencing technologies has enabled the interrogation of genomic variation at a much finer scale, and now allows for an exploration into the diversity of p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 65 publications
3
59
0
Order By: Relevance
“…During endosymbiotic co-evolution, most of the genetic information present in the ancestral mitochondrion has transferred to the nuclear genome (Gray et al 1999;Adams and Palmer 2003;Timmis et al 2004). An apparent burst of mtDNA transfer occurred during primate evolution ∼54 million years ago (Gherman et al 2007) and occasional, probably more recent, transfer in humans has been observed in the germline (Turner et al 2003;Goldin et al 2004;Chen et al 2005;Millar et al 2010;Dayama et al 2014).…”
mentioning
confidence: 99%
“…During endosymbiotic co-evolution, most of the genetic information present in the ancestral mitochondrion has transferred to the nuclear genome (Gray et al 1999;Adams and Palmer 2003;Timmis et al 2004). An apparent burst of mtDNA transfer occurred during primate evolution ∼54 million years ago (Gherman et al 2007) and occasional, probably more recent, transfer in humans has been observed in the germline (Turner et al 2003;Goldin et al 2004;Chen et al 2005;Millar et al 2010;Dayama et al 2014).…”
mentioning
confidence: 99%
“…Complementary in vitro replication assays of the small origin of light strand replication were able to demonstrate that mutations decreased replication efficiency, implying that these missing mutations were likely to have been copied less, creating the illusion of a reduced mutation rate in the mouse 61 . However, the analysis of these naturally occurring human mutations must be confirmed by additional studies, especially in light of the individual-by-individual variation in the number of copies of mitochondrial pseudogenes (NUMTs 45 ) found within the nuclear DNA 46 , which may confound short-read deep-coverage analyses.…”
Section: Haplogroupsmentioning
confidence: 99%
“…Long-read technologies have even greater intrinsic error rates. Using either short-or long-read sequencing technologies, the data can be contaminated with nuclear mitochondrial DNA sequences (NUMTs) 45,46 or DNA base damage, which can appear as real sequence variants. There is evidence of individual-level variation in NUMTs 46 , so when using short-read next-generation sequencing data, these polymorphic NUMTs can be very difficult to filter out in silico.…”
Section: Vegetative Segregationmentioning
confidence: 99%
“…Numts, for nuclear mitochondrial DNA copies (and nupts for the plastid) (94), are typical components of eukaryotic genomes (93)(94)(95) whereas segments of bacterial chromosomes are not. For example, our genomes harbor 53 numts that are specific to the human lineage (96), with 12 numts that are polymorphic in human populations (93), and more numts continuously being found in the human 1,000 Genomes data (97). Five human numts are associated with disease (93), one of which involves a 72-bp numt insertion into exon 14 of the GLI3 gene, causing a premature stop codon, in a rare case of Pallister-Hall syndrome stemming from the Chernobyl incident (98).…”
Section: Supernumerary Symbionts or Inherited Chimerism?mentioning
confidence: 99%